Hubungan Antara Koordinasi Mata Tangan dan Kekuatan Otot Lengan terhadap Ketepatan Hasil Servis atas Bola Voli pada Mahasiswa Pendidikan Jasmani Angkatan 2023 - Peri Gentari Putra; Mimi Haetami; Novi Yanti (Journal on Education, 2025)
This study aims to analyze the relationship between eye-hand coordination and arm muscle strength with the accuracy of the upper serve in volleyball. The method used is a correlational approach, with a sample consisting of 24 physical education students of Tanjungpura University, class of 2023. Data were analyzed using the product-moment correlation test. The results of the analysis show: (1) There is a significant relationship between eye-hand coordination and the accuracy of the upper serve, with a calculated r value ≥ r table (0.442 ≥ 0.404). (2) There is a significant relationship between arm muscle strength and the accuracy of the upper serve, with a calculated r value ≥ r table (0.496 > 0.404). (3) There is a significant relationship between eye-hand coordination and arm muscle strength to the accuracy of the upper serve, with a calculated r value of 0.572 indicating a moderate correlation.